2019
DOI: 10.1002/cncr.32538
|View full text |Cite
|
Sign up to set email alerts
|

Platinum exposure and cause‐specific mortality among patients with testicular cancer

Abstract: BACKGROUND: Although testicular cancer (TC) treatment has been associated with severe late morbidities, including second malignant neoplasms (SMNs) and ischemic heart disease (IHD), cause-specific excess mortality has been rarely studied among patients treated in the platinum era. METHODS: In a large, multicenter cohort including 6042 patients with TC treated between 1976 and 2006, causespecific mortality was compared with general population mortality rates. Associations with treatment were assessed with propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
40
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 43 publications
(83 reference statements)
13
40
1
Order By: Relevance
“…Among the 23 patients with CS II disease (ie, radiation therapy with curative intent), 18 (78%) patients had CS II at diagnosis, whereas 5 patients (22%) had metachronous relapses after active surveillance. Patients with CS I, IIA, and IIB received a median total radiation dose of 25 Gy (95% CI, 23-27), 32 Gy (95% CI, [30][31][32][33][34][35], and 36 Gy (95% CI, 31-37), respectively. Among 22 of the 23 CS II patients assessable for response, radiation therapy response categories were complete remission (CR), tumor-marker negative partial remission (PRm−), and progressive disease (PD) in 16 (73%), 3 (14%), and 3 (14%) cases, respectively.…”
Section: Analysis From Time Of Initial Radiation Therapy In Adjuvant ...mentioning
confidence: 99%
“…Among the 23 patients with CS II disease (ie, radiation therapy with curative intent), 18 (78%) patients had CS II at diagnosis, whereas 5 patients (22%) had metachronous relapses after active surveillance. Patients with CS I, IIA, and IIB received a median total radiation dose of 25 Gy (95% CI, 23-27), 32 Gy (95% CI, [30][31][32][33][34][35], and 36 Gy (95% CI, 31-37), respectively. Among 22 of the 23 CS II patients assessable for response, radiation therapy response categories were complete remission (CR), tumor-marker negative partial remission (PRm−), and progressive disease (PD) in 16 (73%), 3 (14%), and 3 (14%) cases, respectively.…”
Section: Analysis From Time Of Initial Radiation Therapy In Adjuvant ...mentioning
confidence: 99%
“…In this model, the influence of the implementation of a surveillance program (colonoscopy or FIT) will be simulated. This model can estimate the incidence, prevalence and mortality of CRC, and the results and effects of surveillance based on the prevalence of advanced neoplasia detected during this current study and taking to account the mortality risk of TC survivors [ 30 ]. The costs and number of life-years gained for the population with and without the implementation of surveillance will be evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…Historically, an argument for the use of chemotherapy in this setting was to avoid the risk of secondary malignancy associated with irradiation. Recent data, though, has shown that cisplatin-based chemotherapy carry similar risks of secondary malignancy, as highlighted by Dutch and Norway population-based studies (2.5 and 2.0-3.7-fold increased risk observed, respectively) [19,20]. In addition, late chemotherapy-related toxicities must also be taken into account; including peripheral neuropathy, hearing loss, tinnitus, renal disease, and metabolic syndrome.…”
Section: Relapsed Stage I Seminomamentioning
confidence: 97%